Monoclonal gammopathy of undetermined significance in Chinese population: A prospective epidemiological study. Issue 1 (1st October 2018) - Ma, Ling; Xu, Shuang; Qu, Jianhua; Hou, Jian; Wang, Yang; Wen, Lei; Liu, Yang; Kang, Ying; Jiang, Ming; Fu, Weijun; Du, Juan; Zhou, Lin; et al.
Abstract: The aim of this study was to identify the prevalence of monoclonal gammopathy of undetermined significance (MGUS) in different groups of age and the clinical features in China. This multicenter prospective study enrolled 1797 health subjects. The overall prevalence of MGUS was 2.73%. The prevalence of different age groups was 1.19% (41‐50 y), 1.16% (51‐60 y), 2.19% (61‐70 y), 3.66% (71‐80 y), and 7.76% (≥81 y). The prevalence of MGUS in male (n = 843) was 2.97%, while the prevalence of MGUS in female (n = 952) was 2.52%, but this difference of the two groups was not statistically significant. As for subtype of MGUS, IgG subtype was 55.1% (27 cases), IgA subtype was 14.3%, and IgM subtype was 12.2%. The M protein of one case became negative after 3 months, and the others remained positive without obvious disease transformation (follow‐up duration: 3‐7 mo). Thus, the prevalence of MGUS in China was similar to that in Mexican Americans, but lower than that in the other Asian country, American Whites, American Blacks, and Africans, and had a trend of increase with age. Male had higher prevalence of MGUS in China. The most common subtype was IgG.